DEVONIAN STRATIGRAPHY OF MONGOLIAN ALTAI - Oleneva N.V. (My University, 1997)
In the Mongolian Altai, thick and widespread Devonian deposits were initially divided into two large stratigraphic complexes; the lower subdivision spanned the Eifelian Stage, and the upper one corresponded to the summary interval of the Givetian Stage and Upper Devonian. New paleontological materials provided grounds to subdivide these deposits into lower Emsian, upper Emsian-Eifelian, Givetian, Frasnian, and Famennian bed sequences. Data on organic remains from Upper Devonian deposits are presented for the first time.
Keywords: Devonian; Paleozoic::Devonian; Палеозой::Девонская